Evaluasi Implementasi PWA terhadap Performa Website dengan Lighthouse dan Chrome DevTools - Siregar, Master Edison (Algoritme Jurnal Mahasiswa Teknik Informatika, 2026)
Website performance is a critical determinant of user experience and digital service efficiency. This study evaluates the impact of Progressive Web App (PWA) implementation on performance using Google Lighthouse and Chrome DevTools. Employing a comparative experimental method, tests were conducted across initial and repeat visit scenarios with three iterations ($K=3$). Evaluation parameters included total requests, data transferred, finish time, DOMContentLoaded, load time, and Lighthouse performance scores.The results demonstrate significant improvements following PWA integration. Average data transfer decreased substantially from 3.9 MB to 320.07 kB, while finish time dropped from 8.42 to 7.26 seconds. Furthermore, load time accelerated from 190.33 ms to 59.00 ms. The Google Lighthouse performance score rose from 71 to 91, shifting the classification from "medium" to "good." These findings confirm that PWA effectively enhances website performance by optimizing data transfer efficiency and accelerating repeat access through service worker-based caching mechanisms.